Veterinary drug, 17β-trenbolone promotes the proliferation of human prostate cancer cell line through the Akt/AR signaling pathway. (May 2018) - Lee, Hee-Seok; Jung, Da-Woon; Han, Songyi; Kang, Hui-Seung; Suh, Jin-Hyang; Oh, Hyun-Suk; Hwang, Myung-Sil; Moon, Guiim; Park, Yooheon; Hong, Jin-Hwan; Koo, Yong Eui
Abstract: Trenbolone acetate (TBA) is a synthetic anabolic steroidal growth factor that is used for rapid muscle development in cattle. The absorbed TBA is hydrolyzed to the active form, 17β-trenbolone (17 TB; 17β-hydroxy-estra-4, 9, 11-trien-3-one) in meat and milk products, which can cause adverse health effects in humans. Similar to 5α-dihydrotestosterone (DHT), 17 TB was reported to exhibit endocrine disrupting effects on animals and humans due to its androgenic effect via binding to the androgen receptor. The purpose of this study is to investigate the molecular mechanism of cell proliferation in prostate cancer (PCa) cells treated with 17 TB. We found that 17 TB induces AR-dependent cell proliferation in the human prostate cancer cell line, 22Rv1 in a concentration dependent manner. Treatment with 17 TB increased the expression of cell cycle regulatory proteins, cyclin D2/CDK-4 and cyclin E/CDK-2, whereas the expression of p27 was down-regulated. Furthermore, phosphorylation of Rb and activation of E2F were also induced, which suggests the activation of cyclin D2/CDK-4 and cyclin E/CDK-2 in the cells. When 22Rv1 cells were exposed to 30 pM of 17 TB, which is the effective concentration (EC50 ) value required to observe proliferative effects on 22Rv1 cells, the expression levels of the phosphorylated forms of Akt and GSK3β were increased. This study demonstrates that 17 TB induces AR-dependent proliferation through the modulation of cell cycle-related proteins in the Akt signaling pathway. The present study provides an effective methodology for identifying cell proliferation signaling of veterinary drugs that exert AR agonistic effects. Highlights: 17 TB is hydrolyzed form of veterinary drug, Trenbolone acetate. 17 TB residues in meat and milk products could cause adverse effects in humans. We found mechanism of proliferation of human prostate cancer cell, 22Rv1 by 17 TB. 17 TB promotes the proliferation of 22Rv1 line through Akt/AR signaling pathway.